Solitary wave of ground state type for a nonlinear Klein-Gordon equation coupled with Born-Infeld theory in R - Albuquerque Francisco S. B. (Electronic journal of qualitative theory of differential equations, 2020)
In this paper we prove the existence of nontrivial ground state solution for a nonlinear Klein–Gordon equation coupled with Born–Infeld theory in R2 involving unbounded or decaying radial potentials. The approach involves variational methods combined with a Trudinger–Moser type inequality and a symmetric criticality type result.